2010
DOI: 10.1111/j.1600-0897.2010.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated NK Cell Cytotoxicity, CD158a Expression in NK Cells and Activated T Lymphocytes in Peripheral Blood of Women with IVF Failures

Abstract: Elevated NKc is negative factor, though not critical for implantation in IVF cycles. Immune mechanism of IVF failure includes not only elevated NKc but also some other factors, such as elevated expression of CD8 and CD158a on NK cells, T lymphocyte activation, and diminished T helper 2 parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
1
26
0
2
Order By: Relevance
“…reported a similar expression of the activation marker CD154 + in the T‐cell population for RIF patients, but a significantly higher expression of CD69 + , although their study group consisted of both RIF patients and patients with RSM . However, a study comparing different cell subsets in a prospective cohort design showed a higher expression of HLA‐DR on T cells in women with RIF that became pregnant in the following attempt …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…reported a similar expression of the activation marker CD154 + in the T‐cell population for RIF patients, but a significantly higher expression of CD69 + , although their study group consisted of both RIF patients and patients with RSM . However, a study comparing different cell subsets in a prospective cohort design showed a higher expression of HLA‐DR on T cells in women with RIF that became pregnant in the following attempt …”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies indeed showed that the immune reactivity in women with recurrent pregnancy losses is different as reflected by higher T‐helper cells 1 (Th1)/Th2 ratios in the peripheral blood of women with recurrent implantation failure (RIF), defined as repeated consecutive failure of high‐quality embryos to implant (following three attempts of IVF), and women with recurrent spontaneous miscarriages (RSM) . Furthermore, peripheral T cells from patients with implantation failure express higher levels of the activation markers HLA‐DR, CD154, and CD69 . T cells with immune suppressive functions are pivotal for an appropriate immune regulation, and only recently the essential role of these regulatory T cells in pregnancy has been appreciated .…”
Section: Introductionmentioning
confidence: 99%
“…During implantation, maternal immunoactivation and tolerance not only are limited to the decidua but are also observed in the periphery. 8,9 Our patient was found to have an immunophenotypic profile that included increased percentages of central memory and activated CD4+ T-cells coexpressing the alpha chain of the IL-2 receptor which might be surrogates of increased T-helper 1 (Th1) immunity. CD4+ central memory cells contain a higher number of Th1 (IFN-g producing) cells.…”
Section: Discussionmentioning
confidence: 98%
“…Cytokines are immunoregulatory molecules with a crucial responsibility for determining the nature of immune response. It has been proposed that the cytokine turnover toward the Th2 immune response is supportive of successful pregnancy, whereas Th1 type cytokines impair it 9,16–19 . However, recent studies have shown that Th1 cytokines are not always detrimental for pregnancy development and that they could have a positive role in a successful pregnancy 11–13 .…”
Section: Discussionmentioning
confidence: 99%